THE ATTITUDES AND OPINIONS OF THE TEACHING STAFF CONCERNING INCLUSION IN THE CZECH REPUBLIC: READINESS FOR CHILDREN WITH VARIOUS TYPES OF IMPAIRMENT - Baslerova, Pavlina; Ruzicka, Michal; Michalik, Jan (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The paper focuses on a part of an extensive research study of the attitudes of teachers in kindergartens, elementary and secondary schools in the Czech Republic to the amendment to the Education Act effective from 1 September 2016, which introduced a new model of assessment of special educational needs.According to the amendment, children with SEN are no longer assessed by the type of disability (health, social), but rather by the impact of the disability on their educational needs. These are newly classified into five degrees of ‘support measures’.The amendment and related regulations also significantly limited the activities of schools specially designed for children with mild intellectual disability. By means of a measure issued by the Minister of Education, the curriculum specially formulated for these schools, which forms an annex to the Framework educational programme, was cancelled.These measures caused an unprecedented social discussion, which was often marked by strong anti-inclusion attitudes of the general public. Therefore, in May 2017 the research team of the Faculty of Education, Palacký University in Olomouc carried out an extensive measurement (2xxx respondents), which brought a real picture of teachers’ attitudes to the ongoing changes.The paper presents the attitudes of two groups of respondents: teachers in mainstream schools and teachers in special schools. The results showed statistically significant differences in the attitudes and assessments between these two groups of concerning the issue of inclusive or joint education.